Effectiveness of registered nurses on system outcomes in primary care: a systematic review - Julia Lukewich; Shabnam Asghari; Emily Gard Marshall; Maria Mathews; Michelle Swab; Joan Tranmer; Denise Bryant-Lukosius; Ruth Martin-Misener; Allison A. Norful; Dana Ryan; Marie-Eve Poitras (BMC, 2022)
Abstract Background Internationally, policy-makers and health administrators are seeking evidence to inform further integration and optimal utilization of registered nurses (RNs) within primary care teams. Although existing literature provides some information regarding RN contributions, further evidence on the impact of RNs towards quality and cost of care is necessary to demonstrate the contribution of this role on health system outcomes. In this study we synthesize international evidence on the effectiveness of RNs on care delivery and system-level outcomes in primary care. Methods A systematic review was conducted in accordance with Joanna Briggs Institute methodology. Searches were conducted in CINAHL, MEDLINE Complete, PsycINFO, and Embase for published literature and ProQuest Dissertations and Theses and MedNar for unpublished literature between 2019 and 2022 using relevant subject headings and keywords. Additional literature was identified through Google Scholar, websites, and reference lists of included articles. Studies were included if they measured effectiveness of a RN-led intervention (i.e., any care/activity performed by a primary care RN within the context of an independent or interdependent role) and reported outcomes of these interventions. Included studies were published in English; no date or location restrictions were applied. Risk of bias was assessed using the Integrated Quality Criteria for Review of Multiple Study Designs tool. Due to the heterogeneity of included studies, a narrative synthesis was undertaken. Results Seventeen articles were eligible for inclusion, with 11 examining system outcomes (e.g., cost, workload) and 15 reporting on outcomes related to care delivery (e.g., illness management, quality of smoking cessation support). The studies suggest that RN-led care may have an impact on outcomes, specifically in relation to the provision of medication management, patient triage, chronic disease management, sexual health, routine preventative care, health promotion/education, and self-management interventions (e.g. smoking cessation support). Conclusions The findings suggest that primary care RNs impact the delivery of quality primary care, and that RN-led care may complement and potentially enhance primary care delivered by other primary care providers. Ongoing evaluation in this area is important to further refine nursing scope of practice policy, determine the impact of RN-led care on outcomes, and inform improvements to primary care infrastructure and systems management to meet care needs. Protocol registration ID PROSPERO: International prospective register of systematic reviews. 2018. ID= CRD42018090767 .